Investigation of SARS-CoV-2 infection and associated lesions in exotic and companion animals. Issue 4 (July 2022) - Rotstein, David S.; Peloquin, Sarah; Proia, Kathleen; Hart, Ellen; Lee, Jeongha; Vyhnal, Kristin K.; Sasaki, Emi; Balamayooran, Gayathriy; Asin, Javier; Southard, Teresa; Rothfeldt, Laura; Venkat, Heather; et al.
Documented natural infections with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in exotic and companion animals following human exposures are uncommon. Those documented in animals are typically mild and self-limiting, and infected animals have only infrequently died or been euthanized. Through a coordinated One Health initiative, necropsies were conducted on 5 animals from different premises that were exposed to humans with laboratory-confirmed SARS-CoV-2 infection. The combination of epidemiologic evidence of exposure and confirmatory real-time reverse transcriptase-polymerase chain reaction testing confirmed infection in 3 cats and a tiger. A dog was a suspect case based on epidemiologic evidence of exposure but tested negative for SARS-CoV-2. Four animals had respiratory clinical signs that developed 2 to 12 days after exposure. The dog had bronchointerstitial pneumonia and the tiger had bronchopneumonia; both had syncytial-like cells with no detection of SARS-CoV-2. Individual findings in the 3 cats included metastatic mammary carcinoma, congenital renal disease, and myocardial disease. Based on the necropsy findings and a standardized algorithm, SARS-CoV-2 infection was not considered the cause of death in any of the cases. Continued surveillance and necropsy examination of animals with fatal outcomes will further our understanding of natural SARS-CoV-2 infection in animals and the potential role of the virus in development of lesions.